RETRACTED: Ram, D. Biodiversity Loss with Habitat and Risk of New Diseases. Biol. Life Sci. Forum 2021, 2, 1 - Darshit Ram (Biology and Life Sciences Forum)
The journal retracts the proceedings paper, titled “Biodiversity Loss with Habitat and Risk of New Diseases” [...]